2017
DOI: 10.1002/adfm.201704079
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitizers for Two‐Photon Excited Photodynamic Therapy

Abstract: Photodynamic therapy (PDT) is a noninvasive protocol for the treatment of various cancers and nonmalignant diseases. Light, oxygen, and photosensitizer (PS) are the essential three elements in a typical PDT process. Currently, there are two major barriers limiting the further development of PDT. One issue is limited tissue penetration, and the other is the lack of high-performance PSs. Therefore, the newly emerging two-photon excited PDT (2PE-PDT) has attracted considerable attention in recent years due to its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 127 publications
(162 reference statements)
1
64
0
Order By: Relevance
“…In addition, 2-photon PDT also improves the spatial selectivity and reduces photodamage to healthy tissues (15,16). The efficiency of 2-photon light absorption, also known as the 2-photon absorption cross-section, is crucial for the therapeutic efficiency of the PSs (15,(17)(18)(19). However, the utility of existing clinical PSs for in vivo 2-photon PDT is hampered due to their low 2photon absorption cross-sections: on the order of 1 to 100 Goeppert Mayer (GM) units (1 GM = 10 −50 cm 4 s photon −1 ) ( [20][21][22].…”
mentioning
confidence: 99%
“…In addition, 2-photon PDT also improves the spatial selectivity and reduces photodamage to healthy tissues (15,16). The efficiency of 2-photon light absorption, also known as the 2-photon absorption cross-section, is crucial for the therapeutic efficiency of the PSs (15,(17)(18)(19). However, the utility of existing clinical PSs for in vivo 2-photon PDT is hampered due to their low 2photon absorption cross-sections: on the order of 1 to 100 Goeppert Mayer (GM) units (1 GM = 10 −50 cm 4 s photon −1 ) ( [20][21][22].…”
mentioning
confidence: 99%
“…Furthermore, when compared to known porphyrin analogues, the interest in replacing the porphyrin by a phthalocyanine as the central core to obtain more fluorescent two-photon oxygen photosensitizers is clearly established. As such, this contribution paves the way for the future development of innovative biphotonic photosensitizers usable in theranostics.Molecules 2020, 25, 239 2 of 30 studying new porphyrin-or phthalocyanine-based molecular assemblies that might efficiently undergo two-photon excitation [10-13] while presenting a significant luminescence, constitutes an appealing goal for researchers interested in developing new photosensitizers for theranostic applications [4,5,[14][15][16]. Along these lines, some of us [17,18] and others [19], independently reported that fluorenyl units, when appended at the meso positions of porphyrins, were particularly suited to enhance the fluorescence quantum yields of this macrocyclic core, most likely by limiting the rate of non-radiative decay via internal conversion [20].…”
mentioning
confidence: 99%
“…As a result, new oxygen photosensitizers with significantly improved brightness over H 2 TPP could be obtained by these means [25]. Furthermore, the presence of several fluorenyl units at the periphery of the central macrocycle also allowed for a significant increase in the two-photon absorption (2PA) cross-section maximum at lowest energy, another very desirable feature when targeting PDT or theranostic applications in the near-infrared (NIR) range [14,15].We can notice that, after having studied these non-conjugated TPP-based porphyrin dendrimers featuring flexible ether linkers (Figure 1), we considered more recently porphyrin dendrimers with conjugated peripheral arms [26]. Thus, a series of meso-substituted porphyrin dendrimers incorporating an increasing number of fluorenyl units, featuring fully conjugated alkynyl linkers, was studied.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Relaxation occurs via the Type I or Type II reaction with molecular oxygen as described previously. 11 Due to the nonlinear behaviour of the absorption process, high peak power lasers such as modelocked Ti:sapphire lasers with femtosecond pulse durations are required to achieve efficient two-photon absorption. 12 Different photosensitizers have been developed for TPE-PDT applications, including porphyrin derivatives, ruthenium complexes, conjugated polymers, and nanoparticles.…”
Section: Introductionmentioning
confidence: 99%